From action to language and back Comment on 'Grounding language in action and perception: From cognitive agents to humanoid robots' by Cangelosi - Rohlfing, Katharina; Wrede, Britta (PHYSICS OF LIFE REVIEWS)

Dynamische und statische Selbstkonzepte von Grundschulkindern. Erste Ergebnisse aus dem Forschungsprojekt SAM-G. Vortrag: Symposium „Theorieorientierte und anwendungsorientierte Grundschulforschung“ anlässlich des 65. Geburtstags von Herrn Prof. Dr. Wolfgang Einsiedler - Hellmich, Frank

Förderung positiver Einstellungen und Interessen bei Kindern im Mathematikunterricht der Grundschule – Ergebnisse aus einer Interventionsstudie. Posterpräsentation auf der 19. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hellmich, Frank; Berger, Jennifer; Fichtler, Philip; Nowak, Miriam

Die Bedeutung von Feedback für die Selbstkonzeptgenese bei Kindern im Grundschulalter. Posterpräsentation auf dem Kongress der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hellmich, Frank; Günther, Frederike

Determinanten für dynamische versus statische Selbstkonzepte bei Kindern im Grundschulalter - Hellmich, Frank

Förderung von Lesestrategien bei Kindern mit Migrationshintergrund. Posterpräsentation auf dem Kongress der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hellmich, Frank; Höntges, Jens

Integration of Action and Language Knowledge: A Roadmap for Developmental Robotics - Cangelosi, Angelo; Metta, Giorgio; Sagerer, Gerhard; Nolfi, Stefano; Nehaniv, Chrystopher; Fischer, Kerstin; Tani, Jun; Belpaeme, Tony; Sandini, Giulio; Nori, Francesco; Fadiga, Luciano; Wrede, Britta; et al. (IEEE Transactions on Autonomous Mental Development)

Appropriate Feedback in Asymmetric Interactions - Wrede, Britta; Kopp, Stefan; Rohlfing, Katharina; Lohse, Manja; Muhl, Claudia (Journal of Pragmatics)
Based on the observation that human-robot interaction is often laborious because the robot's interactional abilities fail to meet the user's expectations, we argue that feedback can play a central role in regulating expectations and mitigating unnecessary disruptions in the flow of conversation. For feedback to be appropriate in this sense, it needs to take situational information into account. This idea stems from interviews with persons with hearing and mental impairments who display perceptual limitations similar to a robot. The results of these interviews indicated that, depending on the goals of the situation, people with hearing impairments used either mediation (clarification) or concealment strategies to keep the interaction going. With this idea in mind, we analyzed human-robot interactions in two different situations - more task-oriented interactions versus more socially driven interactions - and we observed different feedback behaviors in users and their reactions to the robot's behavior. We use these results to derive a scaffold for modeling appropriate feedback in asymmetric interactions (i.e., in human-robot interactions) and briefly discuss some consequences for both the design of human-robot interaction and for theories of grounding. (c) 2010 Elsevier B.V. All rights reserved.

Developing feedback: How children of different age contribute to a tutoring interaction with adults - Vollmer, Anna-Lisa; Pitsch, Karola; Lohan, Katrin Solveig; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning (ICDL), 2010 IEEE 9th International Conference on Development and Learning)
Keywords: tutoring interaction; social interaction; video signal processing; robot systems; paediatrics; neurophysiology; Learning; infant; feedback; biology computing; cognitive capabilities; cognition; children

Discourse and lexical patterns in mothers' speech during spatial tasks: What role do spatial words play? - Choi, Soonja; Rohlfing, Katharina (Japanese / Korean Linguistics)

Exploring vocal-motor synchrony: Maternal intermodal synchrony and rhythmic patterning of interactions with 3-4 month olds. - Nomikou, Iris; Rohlfing, Katharina

Entwicklung und empirische Überprüfung eines phasenübergreifenden Berufsfähig-keitsprofils für angehende Lehrpersonen. - Israel, Georgq; Seifert, Andreas; König, Johannes; Schaper, Niclas; Blömeke, Sigrid (AEPF-Tagung „Mixed Methods in der empirischen Bildungsforschung”)

Contested Public Spheres. Female Activism and Identity Politics in Malaysia - Spiegel, Anna

The Internet – serving the revolution? - Fuchs, Christian (Counterfire)

Internet and Society: Social Theory in the Information Age. Paperback - Fuchs, Christian

Co-editor of the special issue “Capitalist crisis, communication & culture“ - Fuchs, Christian; Schafranek, Matthias; Hakken, David; Breen, Marcus (tripleC (cognition, communication, co-operation))

studiVZ: Social Networking Sites in the Surveillance Society - Fuchs, Christian (Ethics and Information Technology)

Labor in Informational Capitalism and on the Internet - Fuchs, Christian (The Information Society)

Grounding Critical Communication Studies - Fuchs, Christian (Journal of Communication Inquiry)

Theoretical Foundations of the Web: Cognition, Communication, and Co-operation. Towards an Understanding of Web 1.0, 2.0, 3.0 - Fuchs, Christian; Hofkirchner, Wolfgang; Schafranek, Matthias; Raffl, Celina; Sandoval, Marisol; Bichler, Robert (Future Internet)

Social Software and Web 2.0: their Sociological Foundations and Implications - Fuchs, Christian (Handbook of Research on Web 2.0, 3.0, and X.0: Technologies, Business, and Social Applications, Volume II)

Global Media and Global Capitalism - Fuchs, Christian (Indigenous Societies and Cultural Globalization in the 21st Century. Is the Global Village Truly Real?)

Facebook, Web 2.0 und ökonomische Überwachung [Social networking sites, web 2.0 and economic surveillance] - Fuchs, Christian (DuD – Datenschutz und Datensicherheit 7/2010)

Review of “Communication Power“ (Manuel Castells) - Fuchs, Christian (Information, Communication & Society)

Critique of the Political Economy of Web 2.0 Surveillance - Fuchs, Christian

Critical Internet Surveillance Studies and Economic Surveillance - Allmer, Thomas

Der Geist der Askese und die konsumistische Ethik - Hälterlein, Jens (Grenzverschiebungen des Kapitalismus. Umkämpfte Räume und Orte des Widerstands)

Christoph Peters - Müller, Inez (Killy Literaturlexikon. Autoren und Werke des deutschsprachigen Kulturraums. Begründet von Walther Killy)

Capitalist Crisis, Communication, & Culture – Introduction to the Special Issue of tripleC - Fuchs, Christian; Schafranek, Matthias; Hakken, David; Breen, Marcus (tripleC (Cognition, Communication, Co-operation): Journal for a Global Sustainable Information Society)

HCI and Society: Towards a Typology of Universal Design Principles - Fuchs, Christian; Obrist, Marianna (International Journal of Human-Computer Interaction)

Social Networking Sites and Complex Technology Assessment - Fuchs, Christian (International Journal of E-Politics (special issue on “E-Democracy: Online Youth Participation and Engagement”, edited by Dubravka Cecez-Kecmanovic, Ariadne Vromen, Mary Anne Kennan))

Towards a Critical Theory of Alternative Media - Fuchs, Christian; Sandoval, Marisol (Telematics and Informatics (special issue on community media, edited by Nico Carpentier and Salvatore Scifo))

Theoretical Foundations of Defining the Participatory, Co-operative, Sustainable Information Society (PCSIS) - Fuchs, Christian (Information, Communication, and Society)

Critical Globalization Studies: An Empirical and Theoretical Analysis of the New Imperialism - Fuchs, Christian (Science & Society)

New Imperialism: Information and Media Imperialism? - Fuchs, Christian (Global Media and Communication)

Critical Globalization Studies and the New Imperialism - Fuchs, Christian (Critical Sociology)

Alternative Media as Critical Media - Fuchs, Christian (European Journal of Social Theory)

Class, Knowledge, and New Media - Fuchs, Christian (Media, Culture & Society)

Foundations of the Critique of the Political Economy of Surveillance - Fuchs, Christian

How Can Surveillance Be Defined? Remarks on Theoretical Foundations of Surveillance Studies - Fuchs, Christian

Critical Privacy Studies and the Internet - Allmer, Thomas

Alternde Männer zwischen Ohnmacht und Aufbegehren - Katja Lange-Müllers und Monika Marons Prosa über langsame Abschiede - Müller, Inez (Alter und Altern)

Artikel zu "Bend It Like Beckham", "The Champ" und "White Men Can't Jump" - Adelmann, Ralf (Filmgenres: Sportfilm)

Fernsehen als Medium der Kontrollgesellschaft - Adelmann, Ralf (Virtualität und Kontrolle)

Kurze Ketten. Handeln und Subjektkonstitution in Computerspielen - Adelmann, Ralf; Winkler, Hartmut (Ästhetik & Kommunikation)

Rezension von Filk, Christian: Episteme der Medienwissenschaft - Adelmann, Ralf (rezensionen:kommunikation:medien)

Mediennutzung, Medieneinsatz und Lesekompetenz - Schulz-Zander, Renate; Eickelmann, Birgit; Goy, Martin (IGLU 2006 - die Grundschule auf dem Prüfstand. Vertiefende Analysen zu Rahmenbedingungen schulischen Lernens)

Entwicklung von Bildungsstandards für die Medienbildung - Grundlagen und Beispiele - Herzig, Bardo; Grafe, S. (Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0)

Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0.

Medienbildung in Schule und Unterricht. - Tulodziecki, G.; Herzig, Bardo; Grafe, S.